Ilias und Odyssee: zwei Epen, zwei Welten - Szlezák, Thomas Alexander (Peitho. Examina Antiqua, 2017)
The different world views of the authors of the Iliad and the Odyssey are illustrated by selection of verses used by both poets. The role of the gods in the Odyssey precludes the tragic conception of human life that is characteristic of the Iliad.